Features of non-radicular pain chronic syndrome in patients with osteochondrosis of the spine and dynamics in the psychoemotional sphere of patients during treatment with galvanic vestibular stimulation - A. G. Naryshkin; A. M. Sarkisyan; M. A. Maksyutina; T. A. Skoromets; Igor V. Galanin; I. A. Orlov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Recent literature has shown convincing results of cold vestibular stimulation in central pain syndromes. Galvanic vestibular stimulation is an analog of cold vestibular stimulation. Both methods can be combined under the general name of vestibular neuromodulation.Objective: To evaluate the effectiveness of the method of galvanic vestibular stimulation for the treatment of chronic pain syndromes in spinal osteochondrosis.Methods: The study included 46 patients diagnosed with osteochondrosis of the spine in adults with chronic pain syndrome (more than 3 months). Patients were divided into 2 groups. The first group consisted of patients who received only conservative therapy according to clinical recommendations, and the second group consisted of patients receiving similar conservative therapy in combination with a course of galvanic vestibular stimulation. The patients of the first and second groups underwent pain syndrome scaling, as well as a study of the psycho-emotional sphere using a number of psychometric techniques.Results: According to all scales and questionnaires, the patients of the second group had better results than the first group. The results obtained were significantly different not only in terms of pain syndrome assessment scales, but also in terms of the results of the psychometric methods used.Conclusion: Medical treatment combined with a course of anodic galvanic vestibular galvanization significantly improves the quality of life and is more effective in reducing the intensity of pain syndrome in patients with chronic pain syndrome in spinal osteochondrosis, compared with the use of conservative treatment alone.